IMPLEMENTATION OF STRATEGIC MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION AT MAKTUBA AL-MAJIDIYAH ISLAMIC BOARDING SCHOOL - Yusuf, Yusuf; Ismail, Muhammad Zuhri; Afandi, Afandi (Molang: Journal Islamic Education, 2024)
This article examines the improvement of the quality of education at Maktab Nubdzatul Bayan (Maktuba) Al-Majidiyah Islamic Boarding School through the formulation and implementation of effective strategies. This study aims to identify and analyze the strategies implemented by Maktuba Al-Majidiyah Islamic Boarding School in improving the quality of education, as well as evaluating the effectiveness of the implementation of these strategies. This research uses a qualitative approach with a phenomenological design. Data were collected through in-depth interviews, observation, and documentation analysis. Data analysis was conducted through three stages: data reduction, data display, and conclusion drawing. Data validity was tested through credibility, transferability, dependability, and confirmability. Results: Maktuba Al-Majidiyah Islamic Boarding School has formulated a strategy to improve the quality of education that includes developing a vision, mission, and values, as well as analyzing the internal and external environment. This strategy includes long and short-term programs that are carried out through accelerated methods and the development of santri skills. Strategy implementation is supported by adequate budget allocations and training programs to improve the professionalism of the asatidz. Strategy evaluation is carried out thoroughly and continuously, with weekly, bi-weekly, monthly, and annual evaluations. This study makes an important contribution in understanding the formulation and implementation of strategies to improve the quality of education in pesantren. The findings show that a good and directed strategic approach is able to improve the quality of education effectively and efficiently, as well as meet the community's expectations of quality education.